IDENTIFIKASI PENGEMBANGAN FASILITAS STASIUN DAN PENGARUHNYA TERHADAP KARAKTER FASAD BANGUNAN STASIUN KERETA API KEJAKSAN CIREBON - Ika Nofiyani; Dewi Astuti; Rakhmanita, Rakhmanita; Sumaiyah Fitrian Dini (Jurnal Ilmiah Teknik, 2024)
The Train Station is the main requirement needed in the procurement of train transportation modes. Currently, trains are public transportation that is very popular with the public to transport people. The architectural style of the Kejaksan Cirebon Train Station building is a blend of colonial and art deco characteristics with local architectural influences. The colonial style of influence is shown in the form of the facade or appearance of the building. This study uses a qualitative approach to analyze the development of building facilities and their influence on the character of the Kejaksan Train Station building facade as a representation of a building that has the influence of colonial architectural style and cultural heritage objects in Cirebon. The analysis was carried out by identifying the addition of facilities and facade elements in the front area, main entrance and the front of the building facing the road. The purpose of this study is to complete the architectural research of the Cirebon Station building and add to the treasury of architectural science, especially in the research of colonial architecture in station buildings.